2011
DOI: 10.14742/ajet.968
|View full text |Cite
|
Sign up to set email alerts
|

Instructional design for cross-cultural online collaboration: Grouping strategies and assignment design

Abstract: <span>The latest networking technologies have made it easier to provide authentic learning experiences for intercultural collaboration. However, more guidance about how to conduct a successful online, cross-cultural collaboration is needed. The purpose of this study was to investigate the instructional design for forming a cross-cultural group and designing the assignments for online cross-cultural collaboration projects. By investigating two collaborative classes of college students from the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…While collaborative learning traditionally occurs during face-to-face encounters, the SNS offered flexible offcampus interaction with peers. In this study, findings suggest that an increased peer-to-peer interaction achieved the positive outcomes found in previous studies including community cohesion (Barczyk & Duncan, 2013;Wang, 2011) The students developed collegial relationships through the SNS that spilled over into the on-campus domain. Two students with significant extracurricular commitments reported using Facebook to identify like-minded peers in order to form face-to-face skill practice partnerships.…”
supporting
confidence: 64%
“…While collaborative learning traditionally occurs during face-to-face encounters, the SNS offered flexible offcampus interaction with peers. In this study, findings suggest that an increased peer-to-peer interaction achieved the positive outcomes found in previous studies including community cohesion (Barczyk & Duncan, 2013;Wang, 2011) The students developed collegial relationships through the SNS that spilled over into the on-campus domain. Two students with significant extracurricular commitments reported using Facebook to identify like-minded peers in order to form face-to-face skill practice partnerships.…”
supporting
confidence: 64%
“…As regards community building, in one case (Buzzetto‐More, ) Facebook was compared with Blackboard and it was reported that learners found it better for socialization as it strengthens interpersonal relationships. In another study (Wang, ), Facebook emerges as an adequate tool for cross‐cultural collaboration and community building.…”
Section: Resultsmentioning
confidence: 99%
“…In Question 1, just under 10% of the 32 participants reported some degree of dissatisfaction, while the attitude of over 90% of the participants was either neutral (22%), somewhat positive (53%) or very positive (16%). Taking into account the advantages of transnational collaboration highlighted in the literature -such as autonomous learning and in-depth reflection (Chorney 2007), developing intercultural competence (Wang 2011), as well as the specific advantage that authentic interaction in L2 offers to L2 students (Yang and Chen 2014, 57) -such views are not difficult to account for.…”
Section: Discussionmentioning
confidence: 99%
“…botshon 2006, 2014 for a more comprehensive overview of the issue). Research suggests that there is a wide range of advantages to using collaborative writing The term "cross-cultural collaboration" is used in the sense of McLaughlin and Ponte (1997), Wang (2011), Taras et al (2013), , etc. For more detail, cf.…”
Section: Developing Academic Literacy Through Collaborative Writingmentioning
confidence: 99%